Future socio-economic impacts and vulnerability - Osman-Elasha, B.; Parrotta, J.A.; Adger, N.; Brockhaus, Maria; Colfer, C.J.P.; Sohngen, B.; Dafalla, T.; Joyce, L.A.; Nkem, J.; Robledo, C. (IUFRO, 2009)
The projected impacts of climate change are significant, and despite the uncertainties associated with current climate and ecosystem model projections, the associated changes in the provision of forest ecosystem services are expected to be substantial in many parts of the world. These impacts will present significant social and conomic challenges for affected communities and society as a whole, particularly among the forest-dependent poor, who are already highly vulnerable in many countries throughout the world. This chapter discusses how the likely effects of climate-induced changes on the provision of forest ecosystem services may affect the economic and social well-being of society, including forest-dependent people, with specific reference to the production of wood and non-wood products, hydrological regulation and water quality, human health and well-being, spiritual and cultural values, recreation and ecotourism. The role of governance is discussed as a key factor that will profoundly influence social and economic impacts and vulnerabilities, and the adaptive capacity of societies to deal with the effects of expected climate change-induced shifts in the quantity and quality of forest ecosystem services